MUHKAM DAN MUTASYABIH: STUDI TEMATIK SURAH ALI IMRAN AYAT 7 (TELAAH ATAS PENAFSIRAN AL-QURTHUBI DALAM KITAB AL-JAMI' LI AHKAM AL-QUR'AN) - Husna, Nihayatul (IAINU Kebumen Prodi IAT, 2024)
This research focuses on Al-Qurthubi's interpretation of Q.S. Ali Imran verse 7 in his commentary work Al-Jami' Li Ahkam Al-Qur'an. The aim of this research is to understand the rules of muhkam and mutashabih in the Qur'an from Al-Qurthubi's perspective, the causes of muhkam and mutasyabihya, the division of muhkam and mutasyabih verses, and how Al-Qurthubi responds to muhkam and mutasyabih verses. This research is a type of library research because it uses library data sources as a reference. This research is descriptive analytical in nature, where the approach is used to understand the muhkam and mutasyabih verses from Al-Qurthubi's perspective. The results of the research reveal that, according to Al-Qurthubi, muhkamat verses are verses that are clear and unequivocal in meaning, and can be understood easily without the need for takwil to explore their meaning. Meanwhile, the mutasyabihat verses are divided into two categories, first; mutasyabihat mutlaqan, namely verses that in their entirety only Allah knows the meaning and essence. Second; mutasyabihat ghairu mutlaqan, namely verses that can be understood after studying them in depth because of the vagueness of their pronunciation or meaning. Mutasyabihat in terms of pronunciation, such as in verses whose vague pronunciation is gharib, mustrarak, or murakkab. Meanwhile, mutasyabihat in terms of meaning, such as verses from the Qur'an which explain the name of Allah and his attributes, as well as verses which seem contradictory in their own way.